Book review. Steir-Livny, Liat (2017). Is It OK to Laugh about It? Holocaust Humour, Satire and Parody in Israeli Culture. London, Portland, OR: Vallentine Mitchell Publishers. 207 pp. - Alyona Ivanova (The European Journal of Humour Research, 2018)
Book review Steir-Livny, Liat (2017). Is It OK to Laugh about It? Holocaust Humour, Satire and Parody in Israeli Culture. London, Portland, OR: Vallentine Mitchell Publishers. 207 pp.